Ionic liquid dispersive liquid–liquid microextraction for pesticide residue analysis in honey. Issue 4 (7th August 2020) - Zheng, Yan-Zhen; Wang, Kai; Liang, Qin; Xue, Xiao-Feng; Zhao, Liu-Wei; Chen, Da-Fu; Wu, Li-Ming; Guo, Rui; Xiong, Cui-Ling
Abstract : Honey is a kind of directly consumed food and has the image of being natural, healthy, and clean. However, today's honey may be contaminated with pesticides applied in agriculture and distributed in the environment. Ionic liquid-based liquid–liquid microextraction (IL-DLLME) methods combine the advantages of ILs, such as tunable properties, low vapor pressure at room temperature, and lower toxicity (compared to conventional organic solvents), with the advantages of DLLME, such as simplicity of operation, low sample volume, low cost, high recovery, easy operation, low consumption of reagents, high enhancement factor, high preconcentration factors, and shorter analytical time. They are turning into remarkable tools to develop greener sample preparation methods in analytical chemistry. This review focuses on the IL-DLLME techniques used for different pesticide analysis in honey. The advantages, limitations, and future outlook of IL-DLLME method on pesticide analysis in honey are also discussed.